PRODUK INTELEKTUAL KAMPUS BOARD GAME LABIRIN MATEMATIKA: RAGAM MODEL DAN POTENSI PENGGUNANYA - Fathurrohman, Maman; Pamungkas, Aan Subhan; Satyanegara, Diqbal; Putra, Deni Dwi; Lesmana, Rian; Jannah, Fitri Miftakhul; Rucheni, Rucheni; Khoirunisa, Salsa Nashiroh; Gemilang, Adip Putra (Universitas Sultan Ageng Tirtayasa, 2023)
Universitas Sultan Ageng Tirtayasa has a campus intellectual product based on a patent called Labirin; the mathematical board game. The availability of these products enables the development of knowledge-based economy as Campus Intellectual Product. The availability of printed and digital products of the game will enable the commercialization for use by many people. The potential product range and its users are described in this article. Keywords: Patent, Mathematical board game, Intellectual product, Users, Schools